The independence of judges - Engstad, Nils Asbjørn; Frøsetg, Astrid Lærdal; Tønder, Bård. (The Hague : Eleven International Publishing, 2014)
An independent judiciary is crucial for upholding the rule of law and for the protection of human rights in a democratic society. The Independence of Judges is an anthology, illustrating that there is still a need for further exploration and reflection on various aspects of the principle of judicial independence. The book presents 22 articles, written from different perspectives and analyses by judges, lawyers, public prosecutors, and scientists in the areas of law, social sciences, and media science. The book's contributions provide an overview of historical developments, as well as issues of.
The independence of courts and judges and their relationship with the other branches of government / Tore Schei -- Independent courts : a Danish Supreme Court perspective / Børge Dahl -- Requirements concerning the independence of the judiciary according to Norwegian and international law / Jørgen Aall -- On the origins of judicial independence / Eirik Holmøyvik -- The independence of judges / Lord Jonathan Mance -- Judicial independence and the appointment of judges in Norway / Arne Fliflet -- Court management and professional integrity : a Swedish judicial dilemma / Olof Wilske -- Judicial independence in the outskirts of Europe / Nils A. Engstad -- The independence of judges -- and the judiciary -- as seen from Venice / Jan Erik Helgesen -- Judicial independence in Europe : principles and reality / Julia Laffranque -- Establishment of an independent and accountable judiciary in countries in transition : Bosnia and Herzegovina as a case study / Sven Markus Urke -- The independence of judges and confidence in the courts in the Russian Federation / Ketil Lund, Andreas Motzfeldt Kravik and Marianne Nergaard Magnus -- The independence of international judges / Erik Møse -- A speech from a lawyer in practice : the independence of the judiciary and the independence of the legal profession : dependent on each other / Berit Reiss-Andersen -- "Not ... the independence of a judge" : reflections on the position of the Norwegian prosecuting authority as compared to that of the courts, and remarks on international standards for the activities of the prosecuting authority / Knut H. Kallerud -- Judicial power and legal revolution / Øyvind Østerud -- The European Court of Human Rights and the Norwegian Supreme Court : independence and democratic control / Geir Ulfstein and Andreas Føllesdal -- The neutrality and impartiality of judges in a multicultural society / Katja Jansen Fredriksen -- Judicial independence and the rights of Indigenous peoples / Susann Funderud Skogvang -- Judicial independence and judicial responsibility / Hans Petter Graver -- Independent judges and the relationship with the media / Ragna Aarli.
Online resource; title from PDF title page (viewed Apr 14, 2014).
Includes bibliographical references.
English.
eBooks on EBSCOhost
Keywords: Judicial independence; Judges; Separation of powers; Indépendance judiciaire; Séparation des pouvoirs; LAW -- Civil Procedure; LAW -- Legal Services; POLITICAL SCIENCE -- Government -- Judicial Branch; Judges; Judicial independence; Separation of powers; Judges; Judicial independence; Judicial system; National courts; International courts